Performance assessment for liner shipping industry: a multi-attribute analysis by the balanced scorecard (BSC) - Bulut, Emrah; Gao, Zi-Yi; Duru, Okan; Yoshida, Shigeru (Emerald, 2013)
This paper investigates the performance assessment of liner shipping industry and presents a multi-dimensional evaluation framework to ensure both financial and non-financial monitoring. The traditional performance assessment approach is based on the financial indicators such as ratio analysis, but it is limited to the fiscal perspective. The meaning of performance has dramatically changed and non-financial (and intangible) assets increased their importance in recent years. Under these circumstances, the multi-attribute performance assessment methods play a critical role to combine many aspects of the business. Balanced Scorecard (BSC) is originally developed for the multi-attribute performance assessment and its philosophy on business process evaluation pioneered the importance of key performance indicators and the quality management issues including the internal customer. Service quality and the business performance assessment are some of the hot issues in the liner shipping industry and the long term competitiveness is a critical concern in the recent liner shipping business. The BSC method is utilized to ensure a cumulative analysis of the short/long and tangible/intangible indicators of performance and computes the weight of each criterion by using Fuzzy-AHP method in the liner shipping industry.
Keywords: HF1-6182; Commerce